PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN DENGAN KOMITMEN ORGANISASIONAL SEBAGAI VARIABEL INTERVENING (Studi Pada Karyawan Kantor PT. Pos Indonesia Kudus) - Rezky Muhammad, Akhibulha; Rahardja, Edy (Faculty of Economics and Business Diponegoro University, 2021)
The purpose of this study was to determine the effect of variables of Transformational Leadership, Work Motivation, and Organizational Commitment on improving employee performance. Based on company data, it is shown that there was a decline in employee performance in the third and fourth quarter of 2019. The phenomenon of decreasing performance is what underlies this research. Then build an empirical research model of transformational leadership style and work motivation on employee performance at PT. Pos Indonesia Kudus through the concept of organizational commitment.The data used in this study are primary data in the form of distributing questionnaires as many as 50 employee respondents from all departments at PT Pos Kudus. The sampling technique used in this study is probability sampling. The analysis model of this study used the PLS Structural Equation Model and to test the effect of the intervening variables, the specific indirect effect test was used. The results showed that (1) transformational leadership was positive on employee performance. (2) work motivation has a positive effect on employee performance. (3) transformational leadership has a positive effect on organizational commitment. (4) work motivation has a positive effect on organizational commitment. (5) organizational commitment has a negative effect on employee performance.From the results of the intervening test on the specific indirect effect, Organizational Commitment can be an intervening variable between Work Motivation and Employee Performance. This means that employees feel that their Work Motivation is very good and can show that employees have a sense of being motivated in terms of improving work to continue to develop so that inwardly employees have the instinct to increase their capabilities.